Hubungan Disminore dengan Aktivitas Belajar pada Remaja Siswi Kelas X dan XI SMA N Rancakalong - Anggi Saputra; Umi Khasanah; Sri Hayati; Maidartati; Siska Susilawati (LPPM Universitas BSI, 2021)
Primary dysmenorrhea is pain that is felt during menstruation without any abnormalities in the genital organs. Pain is felt before or at the same time as the onset of menstruation and also lasts for several hours. Those who experience primary dysmenorrhea during menstruation will limit their daily activities, especially activities in learning at school. A student who experiences primary dysmenorrhea will certainly feel disturbed in their learning activities, even this often makes them absent or unable to attend school. In addition, it can reduce the quality of life as well. The purpose of this study was to determine